Determinanty zastosowania instytucji audytu w jednostkach nieprowadzących działalności gospodarczej - Bednarek, Piotr (Determinants of Using an Audit in Nonprofit Organizations, 2008)
Audit is a method for developing an opinion or evaluation according to a set of predefined criteria. The aim of this paper is to identify the demand for an audit in nonprofit organizations. In this paper the differences between nonprofit and profit-oriented organizations in terms of management are specified. Next, the definition of auditing and its types are presented. Finally, the main reasons for using an audit in nonprofit organizations are identified.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 32, s. 9-15